Do Patient Demographics and Socioeconomic Status Influence Severity and Time to Diagnosis in Children With Stable Slipped Capital Femoral Epiphysis?. Issue 4 (7th April 2022) - Loder, Randall T.; Sun, Seungyup; Gunderson, Zachary J.
Abstract : Background: The time to diagnosis in stable slipped capital femoral epiphysis (SCFE) is often several months because of nebulous history, symptoms of knee/thigh pain, and Medicaid insurance. This study examined the impact of socioeconomic status and demographics on the time to diagnosis and SCFE severity in Indiana children. Methods: A retrospective review of all patients at a tertiary children's hospital with SCFE from January 2010 through March 2021 was performed. Standard demographic data and type of insurance was collected. Neighborhood Atlas Mapping was used to determine the state decile of the area deprivation index (ADI), a measure of socioeconomic status using 17 variables related to income, employment, education, and housing. Statistical analyses consisted of standard univariate and bivariate analyses; logistic regression analysis was used to determine predictors of a mild SCFE. A P <0.05 was considered statistically significant. Results: There were 142 patients; 81 male and 61 female. The average age was 12.2±1.7 years, lateral epiphyseal shaft angle of 35±19 degrees, and symptom duration of 4.5±5.0 months. There was no correlation between ADI state deciles and lateral epiphyseal shaft angle ( r 2 =0.008) or symptom duration ( r 2 =0.019). Insurance status and race differed by ADI deciles. In the first decile (least disadvantaged), 44% had government insurance and 89% were White; in the 10th decile (most disadvantaged), 95% had government insurance and 38% were White. Predictors of a mild SCFE were female sex [odds ratio (OR): 3.2 [1.5, 7.0]; P =0.004], symptom duration <3 months [OR: 5.3 (2.4, 11.7); P =0.00004], and White race [OR: 2.4 (1.3, 6.2); P =0.01]. Insurance status and ADI were not significant. Conclusions: Contrary to other studies, neither insurance or socioeconomic status were associated with a delay in diagnosis or SCFE severity. The symptom duration in children with SCFE does not appear to be decreasing over the last several decades. Further investigation is required as to why. Level of Evidence: Level III—retrospective comparative study.